Giant mimiviruses escape many canonical criteria of the virus definition. (February 2019) - Colson, P.; Ominami, Y.; Hisada, A.; La Scola, B.; Raoult, D.
Abstract: Background: The discovery of mimivirus in 2003 prompted the quest for other giant viruses of amoebae. Mimiviruses and their relatives were found to differ considerably from other viruses. Their study led to major advances in virology and evolutionary biology. Aims: We summarized the widening gap between mimiviruses and other viruses. Sources: We collected data from articles retrieved from PubMed using as keywords 'giant virus', 'mimivirus' and 'virophage', as well as quoted references from these articles. Content: Data accumulated during the last 15 years on mimiviruses and other giant viruses highlight that there is a quantum leap between these infectious agents, the complexity of which is similar to that of intracellular microorganisms, and classical viruses. Notably, in addition to their giant structures and genomes, giant viruses have abundant gene repertoires with genes unique in the virosphere, including a tremendous set of translation components. The viruses contain hundreds of proteins and many transcripts. They share a core of central and ancient proteins but their genome sequences display a substantial level of mosaicism. Finally, mimiviruses have a specific mobilome, including virophages that can integrate into their genomes, and against which they can defend themselves through integration of short fragments of the DNA of these invaders. Implications: Mimiviruses and subsequently discovered giant viruses have changed the virus paradigm and contradict many virus definition criteria delineated for classical viruses. The major cellular hallmark that is still lacking in giant viruses is the ribosome, including both ribosomal protein and RNA encoding genes, which makes them bona fide microbes without ribosomes.